2018
DOI: 10.1016/j.psyneuen.2018.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of microglia histone acetylation and protein pathways in mice exhibiting inflammation-associated depression-like symptoms

Abstract: The present study of histone acetylation and differential protein abundance furthers the understanding of the long lasting effects of peripheral immune challenges. Our findings offer insights into target proteins and mechanisms that provide clues for therapies to ameliorate inflammation-associated depression-related behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…Rodriguez-Zas reported an association between indoleamine-pyrrole 2,3 dioxygenase 1 (IDO1) deficiency and phagocytosis and, additionally, immune challenges such as Bacille Calmette-Guerin activation of neurotoxic metabolite microglia phagocytic pathways might induce neurodegeneration and depression-like behavior. [28] Our results showed there were 2 hub genes ( PSMD2 and PSMD6 ) associated with Epstein-Barr virus infection. Ford [29] suggested depressive symptoms are linked to Epstein-Barr virus reactivation among Epstein-Barr virus positive female adolescents, but not males.…”
Section: Discussionmentioning
confidence: 82%
“…Rodriguez-Zas reported an association between indoleamine-pyrrole 2,3 dioxygenase 1 (IDO1) deficiency and phagocytosis and, additionally, immune challenges such as Bacille Calmette-Guerin activation of neurotoxic metabolite microglia phagocytic pathways might induce neurodegeneration and depression-like behavior. [28] Our results showed there were 2 hub genes ( PSMD2 and PSMD6 ) associated with Epstein-Barr virus infection. Ford [29] suggested depressive symptoms are linked to Epstein-Barr virus reactivation among Epstein-Barr virus positive female adolescents, but not males.…”
Section: Discussionmentioning
confidence: 82%
“…Histone H2A plays a role in many cell activities such as gene silencing, cell cycle regulation, fatty acid metabolism and apoptosis [27]. Sandra found that Histone H2A was significantly up-regulated in Bacille Calmette-Guerin (BCG)-inoculated mice, indicating that Histone H2A plays a crucial role in inflammation [28]. Nakata found that heat shock could significantly increase the expression of Histone H2A in Hela cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to neurons, astrocytes have been shown to be resistant to apoptosis-induced bystander killing via the Fas-ligand [ 44 ], thus reminding us of the potential to limit the bystander effect via glia. Phagocytes rapidly remove unhealthy cells and debris from damaged tissue to prevent the uncontrolled release of cytokines and inflammation, which has been shown to have a beneficial effect on prolonged social withdrawal, resignation, and anhedonia [ 45 ]. Our data showed that in response to TBI, astrocytes changed to a phenotype with prolonged processes and hypertrophic bodies at 3 and 7 dpi (Fig.…”
Section: Discussionmentioning
confidence: 99%